2014
DOI: 10.2337/dc13-1022
|View full text |Cite
|
Sign up to set email alerts
|

Metformin, but Not Rosiglitazone, Attenuates the Increasing Plasma Levels of a New Cardiovascular Marker, Fibulin-1, in Patients With Type 2 Diabetes

Abstract: OBJECTIVEThe extracellular matrix protein fibulin-1 is upregulated in the arterial wall in type 2 diabetes (T2D) and circulates in increased concentrations in diabetes. Metformin is an antidiabetic drug with beneficial cardiovascular disease effects in diabetes. We hypothesized that metformin would influence the increased level of plasma fibulin-1 in diabetes. RESEARCH DESIGN AND METHODSAfter a 4-week run-in period, 371 eligible patients with T2D were randomized to treatment groups in a factorial design includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
(60 reference statements)
2
10
1
Order By: Relevance
“…A more detailed insight into the interaction between DM, metformin, and collagens will, however, have to await further studies. Nevertheless, the present results fit well to recent observations in a randomized study, where metformin reduced plasma concentrations of the basement membrane protein fibulin-1 independent of glycemia, 23 strongly suggesting that the use of metformin exerts effects in pathways directly involved in vascular matrix production. This notion is moreover compatible with recent experimental results showing that AMPkinase (activated by metformin) is reduced in kidney tissue in experimental DM and that activation of the enzyme (with AICAAR) normalizes matrix accumulation and albuminuria.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A more detailed insight into the interaction between DM, metformin, and collagens will, however, have to await further studies. Nevertheless, the present results fit well to recent observations in a randomized study, where metformin reduced plasma concentrations of the basement membrane protein fibulin-1 independent of glycemia, 23 strongly suggesting that the use of metformin exerts effects in pathways directly involved in vascular matrix production. This notion is moreover compatible with recent experimental results showing that AMPkinase (activated by metformin) is reduced in kidney tissue in experimental DM and that activation of the enzyme (with AICAAR) normalizes matrix accumulation and albuminuria.…”
Section: Discussionsupporting
confidence: 81%
“…22 In addition, we have, in a randomized study, shown that plasma levels of the basement membrane protein fibulin-1 are reduced by metformin, unrelated to the glycemic control. 23 In relation to the development of diabetic complications, it is also of interest that a study recently showed that mitochondrial dysfunction and reduced activated protein kinase (AMPK) activity in DM are involved in the development of matrix accumulation and proteinuria as part of the diabetic kidney complications and that the kidney damage was corrected by another AMPK stimulator, that is, 5-Aminoimidazole-4-carboxamide ribonucleotide. 24 Thus, it can be hypothesized that metformin through AMPK activation may exert beneficial effects on matrix accumulation as part of diabetic vascular complications.…”
mentioning
confidence: 99%
“…The mean fibulin-1 level in our HF population was 57 ± 16 μg/mL, which is slightly higher than the mean level observed in a DM population (46 ± 1.3 μg/mL [19]). Fibulin-1 is a novel biomarker and high concentrations have primarily been reported in patients with aortic stenosis and DM compared to a level of 5.6 (4.1–8.4) μg/mL reported in healthy men [11, 20, 21].…”
Section: Discussioncontrasting
confidence: 71%
“…Scholze et al 's investigation indicated that diabetes was an independent predictor of plasma fibulin-1 after a multivariable regression model. Skov et al 13 reported that plasma fibulin-1 was elevated in diabetic patients during the 2-year follow-up. And metformin treatment markedly reduced plasma fibulin-1 concentrations in those diabetic patients 13.…”
Section: Discussionmentioning
confidence: 99%